Nano-optomechanical nonlinear dielectric metamaterials - Karvounis, Artemios (2015)
By harnessing the resonant nature of localized electromagnetic modes in a nanostructured silicon membrane, an all-dielectric metamaterial can act as nonlinear medium at optical telecommunications wavelengths. We show that such metamaterials provide extremely large optomechanical nonlinearities, operating at intensities of only a few μW per unit cell and modulation frequencies as high as 152 MHz, thereby offering a path to fast, compact, and energy efficient all-optical metadevices.